Design of broadband invisibility cloak with wide angles of illumination - Tang, Zhe (2018)
Invisibility cloak makes invisibility is no longer just the plot of the novel. Based on previous studies, we’ve already known that the carpet cloak, one of the invisibility solutions, can transform a bump into a flat plane. In this study, a carpet cloak will be designed. And the performance of the designed cloak will be tested, especially at broadband and in wide incident angles. Specifically, after the mathematical manipulations, we will verify the effect of the cloak by conducting both two-dimensional and three-dimensional simulations in CST. The calculation process and the simulation results will be involved in this report. And the report will be ended with a conclusion that the designed cloak successfully achieves invisibility at broadband and in wide incident angles.